2014
DOI: 10.1007/s10902-014-9597-1
|View full text |Cite
|
Sign up to set email alerts
|

Positive Feelings at School: On the Relationships Between Students’ Character Strengths, School-Related Affect, and School Functioning

Abstract: The present study was designed to examine the relationships between students' character strengths, school-related affect, positive school functioning (i.e., motivation to learn, interest, and engagement at class), and school achievement following the ''engine model of well-being'' that is focusing on inputs (e.g., personality traits), processes (e.g., moods, emotions), and outcomes (e.g., engagement, accomplishments) within the context of well-being research. A sample of 196 children completed the Values in Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 23 publications
5
99
2
4
Order By: Relevance
“…It is likely that the high intrinsic motivation to learn also leads to better learning outcomes, and that the positive emotions associated with learning additionally foster school achievement (cf. Schutz and Lanehart, 2002 ; Weber et al, 2014 ). In the initial study by Weber and Ruch (2012) , love of learning, perseverance and prudence were among the most important variables in predicting positive classroom behavior and also had an indirect effect on school achievement through positive classroom behavior.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the high intrinsic motivation to learn also leads to better learning outcomes, and that the positive emotions associated with learning additionally foster school achievement (cf. Schutz and Lanehart, 2002 ; Weber et al, 2014 ). In the initial study by Weber and Ruch (2012) , love of learning, perseverance and prudence were among the most important variables in predicting positive classroom behavior and also had an indirect effect on school achievement through positive classroom behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the need for further research, findings suggest some possible implications for such research among emerging adults and post-secondary students in Canada. Based on their research with early adolescents, Weber, Wagner, and Ruch (2016) suggested that researchers should focus on designing interventions for building character strengths (e.g., LaSalle, 2015;White & Waters, 2015), and that this approach might be an important complement to current approaches which focus on addressing students' deficits. The current study suggests that an approach intended to build perseverance might also be worthy of exploration in post-secondary contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The current study suggests that an approach intended to build perseverance might also be worthy of exploration in post-secondary contexts. Past research linking perseverance to students' positive feelings about school (Weber et al, 2016) and college satisfaction (Lounsbury et al, 2009) suggests the possibility of benefits beyond school success.…”
Section: Discussionmentioning
confidence: 99%
“…It is stressed that the use of metacognitive strategies such as critical thinking, seeking help, timemanagement, deepening and organizing would reduce students' academic anxiety and develops positive emotions toward school (Savia, 2008;Sakız, 2014). Various studies have expressed a relation between positive emotions such as self-esteem, self-efficacy, optimism and hope and adolescents' academic success (Ciarrochi, Heaven and Davies, 2007;Snyder et al, 2002;Weber, Wagner and Ruch, 2016;Yılmaz, Yiğit and Kaşarcı, 2012). Although self-regulation and metacognition show similarities in terms of mutual processes and include components needed for academic success, it is believed that metacognition is fundamentally required for learning to occur and transform this process into positive attitudes and behavior toward learning.…”
Section: Turkish Studies -Educational Sciencesmentioning
confidence: 99%